Stuart Little - Davis, Geena; Lipnicki, Jonathan; Laurie, Hugh, 1959-; Minkoff, Rob.; White, E. B. (Elwyn Brooks), 1899-1985.; Wick, Douglas; Columbia Pictures; Columbia TriStar Home Entertainment (Firm) (Culver City, CA : Columbia/Tristar Home Video, 2002)
The Little family adopts an spunky boy named Stuart who looks a lot like a mouse. Mr. and Mrs. Little adore their new son, but their older son George isn't so sure what to make of his new brother and devises a plan to get Stuart out of the house.
Title from disc label.
Originally released as a motion picture in 1999.
Based on the book Stuart Little by E.B. White.
Special features: exclusive sneak peek at "Stuart Little 2 " ; "A little look with Stuart" game ; subtitles in English ; Stuarts Central Park adventure game ; bloopers & gag reel ; visual effects gag reel ; Making it big HBO special ; Race with Stuart, Hasbro interactive ROM game ; director and animation supervisor's commentary ; visual effects supervisor's commentary, visual effects interactive featurette ; read-along with Stuart ; artists' screen tests ; DVD ROM and Weblinks ; Boat race, early concept reel with director's commentary ; art galleries ; talent files ; theatrical trailers ; scene selections.
Geena Davis, Hugh Laurie, Jonathan Lipnicki.
Rated PG.
Keywords: Comedy films; Animated films; Feature films; Video recordings for the hearing impaired